La complexité des systèmes alimentaires : un atout pour la sécurité alimentaire? - Stéphane Fournier; Jean-Marc Touzard (VertigO)
The paper argues that the diversity of food systems and food models can promote food security, and should be recognized and supported through appropriate governance. The impact of the agro-industrial model in the food system is first presented. The development of mass food production, distributed globally at low prices, contributed to increase the food availability, but negatives have been noted, such as marginalization of farmers, nutritional failures or degradation of natural resources. Food security calls to overcome the challenge of food availability by promoting population's access to safe and responsible food, and by building more sustainable food systems. The potential role of food models diversity is analyzed through a typology which distinguishes the agribusiness model from domestic model, proximity model, commodity model and a range of differentiated quality models. Concrete food systems are marked by a combination of these models, which can fulfill different functions in relation to food security issues. "Alternative" models can enable market access for disadvantaged producers, mitigation of global food chains risks, or preservation of cultural heritage... They also play a key role in consumer food education and contribute to global dynamic of innovation in food systems.